Tales from English history : for children - Strickland, Agnes, 1796-1874 (C.S. Francis & Co. ; Crosby, Nichols & Co., 1854)
"It is the object of the present work to offer the Young a series of moral and instructive tales, each founded on some striking authentic fact in the annals of English History, in which royal or distinguished children were engaged."--Preface p. 6.